College of Education Graduate Tracer Study (GTS): Boon or Bane? - T. Rojas, Teresita; C. Rojas, Rey (European Scientific Journal, ESJ, 2016)
This study traced the employment profile of Cebu Technological University, Main Campus-College of Education (CTU MC CoE) graduates, from 2005-2009. Mix methods of descriptive survey method and thematic analysis were used to trace their status of employment, with the use of questionnaire and personal interviews. Data were analyzed of simple percentages and chi-square for significance of relationship. Illuminating were extrapolated and numbered. It aimed to: ascertain the profile of graduates; determine a relationship between their present occupation and the course they finished; and identify the cooperating industries/institution that employed BEEd and BSEd graduates. The CTU MC CoE graduates were proven to proficient and competent to be employable in the government schools as revealed in the 7 illuminating themes, thus resulted in boon opportunities. High school teachers predominate on the track than the elementary teachers with a negligible difference. The CTU mandate, as cascaded in its vision-mission, prepared graduates for the field of work, with personality that matters compared than other predetermined factors. Academic preparation and career performance exhibited signification of successful teaching employment in the public school.